2019
DOI: 10.1136/injuryprev-2019-043418
|View full text |Cite
|
Sign up to set email alerts
|

Injuries associated with electric-powered bikes and scooters: analysis of US consumer product data

Abstract: BackgroundPowered, two-wheeled transportation devices like electric bicycles (E-bikes) and scooters are increasingly popular, but little is known about their relative injury risk compared to pedal operated bicycles.MethodsDescriptive and comparative analysis of injury patterns and trends associated with E-bikes, powered scooters and pedal bicycles from 2000 to 2017 using the US National Electronic Injury Surveillance System.ResultsWhile persons injured using E-bikes were more likely to suffer internal injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 14 publications
7
60
0
Order By: Relevance
“…DiMaggio et al indicated that while there is some nuance and complexity to the injury picture for these vehicles, there is cause for concern 2 . Injury patterns for E‐bike and P‐scooters differ from each other and from traditional pedal operated bicycles in ways that will demand increased attention from transportation and public health officials 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DiMaggio et al indicated that while there is some nuance and complexity to the injury picture for these vehicles, there is cause for concern 2 . Injury patterns for E‐bike and P‐scooters differ from each other and from traditional pedal operated bicycles in ways that will demand increased attention from transportation and public health officials 2 .…”
Section: Discussionmentioning
confidence: 99%
“…DiMaggio et al indicated that while there is some nuance and complexity to the injury picture for these vehicles, there is cause for concern 2 . Injury patterns for E‐bike and P‐scooters differ from each other and from traditional pedal operated bicycles in ways that will demand increased attention from transportation and public health officials 2 . The increased proportion of concussions reported by DiMaggio et al 2 as well as the high frequency of oral and maxillofacial injuries seen in this current report may be due, at least in part, to the lack of use of helmets and other protective measures by E‐bike and P‐scooter users.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations